Right ventricular function during exercise in children after heart transplantation. (23rd June 2017) - Cifra, B; Morgan, C T; Dragulescu, A; Guerra, V C; Slorach, C; Friedberg, M K; Manlhiot, C; McCrindle, B W; Dipchand, A I; Mertens, L
Abstract: Aims: Right ventricular (RV) dysfunction is a common problem after heart transplant (HTx). In this study, we used semi-supine bicycle ergometry (SSBE) stress echocardiography to evaluate RV systolic and diastolic reserve in paediatric HTx recipients. Methods and results: Thirty-nine pediatric HTx recipients and 23 controls underwent stepwise SSBE stress echocardiography. Colour tissue doppler imaging (TDI) peak systolic (s') and peak diastolic (e') velocities, myocardial acceleration during isovolumic contraction (IVA), and RV free wall longitudinal strain were measured at incremental heart rates (HR). The relationship with increasing HR was evaluated for each parameter by plotting values at each stage of exercise versus HR using linear and non-linear regression models. At rest, HTx recipients had higher HR with lower TDI velocities (s': 5.4 ± 1.7 vs. 10.4 ± 1.8 cm/s, P  < 0.001; e': 6.4 ± 2.2 vs.12 ± 2.4 cm/s, P  < 0.001) and RV IVA values (IVA: 1.2 ± 0.4 vs. 1.6 ± 0.8 m/s 2, P  = 0.04), while RV free wall longitudinal strain was similar between groups. At peak exercise, HR was higher in controls and all measurements of RV function were significantly lower in HTx recipients, except for RV free wall longitudinal strain. When assessing the increase in each parameter vs. HR, the slopes were not significantly different between patients and controls except for IVA, which was lower in HTx recipients. Conclusion: In pediatric HTx recipients RV systolic and diastolic functional response to exercise is preserved with a normal increase in TDI velocities and strain values with increasing HR. The blunted IVA response possibly indicates a mildly decreased RV contractile response but it requires further investigation.